2004
DOI: 10.1002/hed.10401
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p27BBP in head and neck carcinomas and their lymph node metastases

Abstract: Background. p27 BBP is a regulator of ribosome assembly and an essential nuclear and cytoplasmic component of eukaryotes.Methods. We investigated the immunochemical distribution of p27 BBP in head and neck carcinomas, in the associated normal mucosa, and in regional lymph nodes.Results. p27 BBP is detectable in mucosal cells but is overexpressed in carcinomas, highly concentrated in large polymorphous nucleoli, and even larger and more evident in lymph node metastatic foci. Western blotting confirms increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…In partial keeping with this observation, eIF6 down-regulation in pre-B-cells reduced the S-phase fraction and increased the G0/G1 fraction, thereby impairing mitotic cycle progression (Miluzio et al, 2011). In accordance with our results, the high eIF6 expression observed in dysplastic carcinomas suggests that eIF6 is involved in the transition to malignancy by impairing the cell's differentiated capacity (Rosso et al, 2004). Thus the partially hindered mitotic cell cycle progression in eIF6 +/− fibroblasts may favor their differentiation into myofibroblasts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In partial keeping with this observation, eIF6 down-regulation in pre-B-cells reduced the S-phase fraction and increased the G0/G1 fraction, thereby impairing mitotic cycle progression (Miluzio et al, 2011). In accordance with our results, the high eIF6 expression observed in dysplastic carcinomas suggests that eIF6 is involved in the transition to malignancy by impairing the cell's differentiated capacity (Rosso et al, 2004). Thus the partially hindered mitotic cell cycle progression in eIF6 +/− fibroblasts may favor their differentiation into myofibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, eIF6 overexpression has been reported to cause an aberrant eye development in X. laevis (Miluzio et al, 2011). Furthermore, eIF6 overexpression has been found in selected cancer types, such as colorectal carcinomas (Sanvito et al, 2000), head and neck cancer (Rosso et al, 2004), and malignant mesothelioma (Biffo et al, 1997). It has been proposed that eIF6 is a rate-limiting controller of the initiation of translation, able to affect tumorigenesis and tumor growth (Gandin et al, 2008) and that the impairment of eIF6 activity in cytoplasm restricts lymphomagenesis and tumor progression (Miluzio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, eIF6 was found overexpressed in colon rectal cancer, with peaks in metastatic disease (up to ten-fold) [59], head and neck cancer [54], lung metastasis [36] and acute promyelocytic leukemia [25]. Consistently with the model by which Rack1/PKC complex phosphorylates eIF6, thus promoting 80S joining and activating translation, cancer development is also stimulated by Rack1 and PKCβII.…”
Section: Eif6 In Cancermentioning
confidence: 67%
“…24,25 The mechanism of eIF6 overexpression may be due to gene amplification. Human eIF6 is mapped to chromosome 20 (20q12), and previous studies [26][27][28][29][30] have identified amplification of the chromosomal region 20q12-13 in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%